Augmenter of liver regeneration enhances cell proliferation through the microRNA‐26a/Akt/cyclin D1 pathway in hepatic cells. Issue 11 (25th July 2019) - Gupta, Parul; Sata, Teja Naveen; Ahamad, Naushad; Islam, Rakibul; Yadav, Ajay K.; Mishra, Amit; Nithyananthan, Subramaniyam; Thirunavukkarasu, Chinnasamy; Sanal, M.G.; Venugopal, Senthil K.
Abstract : Aim: Hepatocytes can proliferate and regenerate when injured by toxins, viral infections, and so on. Augmenter of liver regeneration (ALR) is a key regulator of liver regeneration, but the mechanism is unknown. The role of ALR in other cell types is not known. In the present study, we investigated the relationship between microRNA (miRNA)‐26a and ALR in the Huh7 cell line and adipose tissue‐derived mesenchymal cells from chronic liver disease patients and healthy individuals. Methods: Huh7 cells were transfected independently with ALR and miRNA‐26a expression vectors, and their effects on cell proliferation, the expression of miRNA‐26a, and activation of the phosphatase and tensin homolog and Akt signaling pathways were determined. The experiments were repeated on mesenchymal stem cells derived from healthy individuals and chronic liver disease patients to see whether the observations can be replicated in primary cells. Results: Overexpression of ALR or miRNA‐26a resulted in an increase of the phosphorylation of Akt and cyclin D1 expression, whereas it resulted in decreased levels of p‐GSK‐3β and phosphatase and tensin homolog in Huh7 cells. The inhibition of ALR expression by ALR siRNA or anti‐miR‐26a decreased the Akt/cyclin D1 signaling pathway, leading to decreased proliferation. Mesenchymal stem cells isolated from the chronic liver disease patients had a higher ALR expression, while the mesenchymal stem cells isolated from healthy volunteers responded to the growth factor treatments for increased ALR expression. It was found that there was a significant increase in miRNA‐26a expression and proliferation. Conclusions: These data clearly showed that ALR induced the expression of miRNA‐26a, which downregulated phosphatase and tensin homolog, resulting in an increased p‐Akt/cyclin D1 pathway and enhanced proliferation in hepatic cells.